Reproducibility of 20-min Time-trial Performance on a Virtual Cycling Platform - Matta, Guilherme; Edwards, Andrew; Roelands, Bart; Hettinga, Florentina; Hurst, Philip (International Journal of Sports Medicine, 2022)
This study aimed to analyse the reproducibility of mean power output during 20-min cycling time-trials, in a remote home-based setting, using the virtual-reality cycling software, Zwift. Forty-four cyclists (11 women, 33 men; 37±8 years old, 180±8 cm, 80.1±13.2 kg) performed 3×20-min time-trials on Zwift, using their own setup. Intra-class correlation coefficient (ICC), coefficient of variation (CV) and typical error (TE) were calculated for the overall sample, split into 4 performance groups based on mean relative power output (25% quartiles) and sex. Mean ICC, TE and CV of mean power output between time-trials were 0.97 [0.95–0.98], 9.4 W [8.0–11.3 W], and 3.7% [3.2–4.5], respectively. Women and men had similar outcomes (ICC: 0.96 [0.89–0.99] vs. 0.96 [0.92–0.98]; TE: 8.3 W [6.3–13.1] vs. 9.7 W [8.2–12.2]; CV: 3.8% [2.9–6.1] vs. 3.7% [3.1–4.7], respectively), although cyclists from the first quartile showed a lower CV in comparison to the overall sample (Q1: 2.6% [1.9–4.1] vs. overall: 3.7% [3.2–4.5]). Our results indicate that power output during 20-min cycling time-trials on Zwift are reproducible and provide sports scientists, coaches and athletes, benchmark values for future interventions in a virtual-reality environment.
Keywords: reliability; virtual training; remote exercise; exercise testing; test-retest